Studies in Coptic culture : transmission and interaction - Ayad, Mariam F. (The American University in Cairo Press, 2016)
Coptic contributions to the formative theological debates of Christianity have long been recognized. Less well known are other, equally valuable, Coptic contributions to the transmission and preservation of technical and scientific knowledge, and a full understanding of how Egypt's Copts survived and interacted with the country's majority population over the centuries. Studies in Coptic Culture attempts to examine these issues from divergent perspectives.